PENGARUH KEAHLIAN DAN PROSES PRODUKSI TERHADAP KUALITAS PRODUK CV. ORIBEAN COFFEE - Dani Saputra; Arief Syah Safrianto (Jurnal Ekonomi dan Industri, 2023)
This study aims to determine the effect of Skills and Production Processes on Product Quality at CV. Oribean Coffee. This research is included in the category of causal associative research using a quantitative approach. The research was carried out by distributing questionnaires to respondents who were all CV. Oribean Coffee. The sampling technique used in this research was saturated sampling. The research method uses simultaneously and partially linear regression analysis. Based on the results of the study it can be concluded that skill and production process simultaneously and partially have a positive and significant effect on product quality.